CEO Equity Incentives and Financial Misreporting: The Role of Auditor Expertise - Jayaraman, Sudarshan; Milbourn, Todd (The Accounting Review, 2015)
ABSTRACT Prior studies find inconsistent evidence regarding the effect of CEO equity incentives on financial misreporting. We argue that this inconsistency stems from not considering detection mechanisms that mitigate the effect of equity incentives on misreporting by limiting the ability of managers to carry out such manipulative activities. Using auditor industry expertise as one such detection mechanism, we document that CEO equity incentives are positively associated with misreporting only in subsamples where auditor expertise is low, but not where expertise is high. The implication of these results is that auditor expertise lowers the cost of granting equity-based incentives and that firms audited by an industry expert grant their CEOs greater equity incentives. We find strong evidence in favor of this implication. Controlling for previously identified determinants of CEO equity incentives, we find that firms audited by an industry expert grant their CEOs 14 percent more equity incentives than firms audited by a non-expert. To address endogeneity concerns, we use the collapse of Arthur Andersen as a quasi-natural experiment and find analogous evidence. Overall, our study documents the critical role of detection mechanisms in the link between CEO contracting and financial misreporting.